Problems of Development of the Medical Industry in Ukraine in the Context of the Decentralisation Reform - Yurii Baiun (Науковий вісник Мукачівського державного університету. Серія Економіка, 2021)
The relevance of the study lies in the fact that the reform of the medical industry is an important component of decentralisation. The old model of functioning of medical institutions is inefficient, so there is a need for reorganisation, which is carried out by making appropriate decisions. The medical industry is one of the most problematic in Ukraine, especially with regard to the organisation of medical care in territorial communities. Therefore, reform in the context of decentralisation is quite a complex process to solve and implement. The reform of the medical industry provides for the creation of a new system of territorial organisation, the development of local self-government, and the improvement of regional state policy. The development of the medical industry is one of the main factors for achieving the well-being of the population and national security. Most medical institutions are low-duty hospitals that have outdated technical equipment and worn-out fixed assets. It is necessary to introduce new approaches to solving public health problems. The purpose of the study is to identify the main problems that negatively affect the development of the medical industry in Ukraine in the context of the implementation of the decentralisation reform. Decentralisation represents the ability of communities to manage resources and have the authority to implement them. The mechanism of decentralisation reform provides for the redistribution of financial resources and power from central state authorities to regional or local self-government bodies. The reform of the medical industry provides for concrete steps to improve the quality of life and services provided, it has a conceptual content and a clear framework. In the process of decentralisation, a wide range of regional policy and local government reforms is being implemented. Its achievements include reducing corruption, improving governance, and activisation of communities. However, it is worth emphasising that this process is accompanied by numerous problems, challenges, and risks in the medical system that need to be finalised and taken into account for further successful implementation. The practical importance lies in identifying problematic factors in the development of the medical system and establishing relationships that hinder health care reform